Synthesis of Uniform Polymer Encapsulated Organic Nanocrystals through Ouzo Nanocrystallization. Issue 1 (10th November 2021) - Middha, Eshu; Chen, Chengjian; Manghnani, Purnima Naresh; Wang, Shaowei; Zhen, Shijie; Zhao, Zujin; Liu, Bin
Abstract: Nanocrystals (NCs) are widely used in optoelectronics, photocatalysis, and bioimaging. As the surface area to volume ratio increases with a decrease in the size of NCs, strategies to control the size of NCs are highly valuable for many applications. Given the importance of photoluminescent dyes, especially those with aggregation‐induced emission, the transformation from an amorphous to a crystalline state can yield a drastic enhancement in their optical properties, which is of significance for biomedical applications. Till now, there is no general method available for the synthesis of small NCs with accurate control over the size and uniformity. Herein, a simple and general approach of ouzo nanocrystallization is presented for the synthesis of small (<100 nm) and highly uniform (polydispersity index 0.1) NCs with good control over the size. The process of nanoprecipitation is used to synthesize uniform nanoparticles (NPs) with different size, which is followed by solvent addition to form swollen NPs. Further, the amorphous core of swollen NPs is converted into NCs within polymer shell under Ouzo zone, which restricts NCs to grow above certain size. To demonstrate the general applicability of ouzo nanocrystallization, two different classes of luminescent materials are used as examples to fabricate small and highly uniform NCs. Abstract : Nanocrystals have shown tremendous progress and great promises in biomedical, photocatalytic, and optoelectronic applications. Till now, methods available for the synthesis of polymer encapsulated nanocrystals are slow, lack controllability, and are not generic. In this study, we present the method of ouzo crystallization for fast, systematic, and controlled synthesis of small organic NCs (<100 nm) with high uniformity (PDI 0.1).